Monitoring Nitrogen Leaching for the Evaluation of the Dutch Minerals Policy for Agriculture in Clay Regions - Dico Fraters; Leo J.M. Boumans; Ton C. van Leeuwen; Wim D. de Hoop (The Scientific World Journal)
This paper presents the results of the Dutch monitoring program for agriculture in the clay regions for the period 1996–2000 and evaluates the monitoring strategy. A wide range of farms (25 to 85%) had a NO3–-N concentration in tile drainwater higher than the EU standard of 11.3 mg/l. The low figure is related to wet winters; the high, to dry winters. Arable farms are more prone to NO3– leaching than dairy farms. On arable farms, about 25% of the N surplus leached to groundwater and tile drainwater, on dairy farms this was about 15%. N in tile drainwater has shown to be the best indicator for monitoring the effects of farming practice changes in the clay regions. The average NO3–-N concentration in tile drainwater was 18.8 and 3.2 mg/l in borehole water on farms where both were monitored. It is known that N use has a relationship with NO3– in tile drainwater and not with NH4+ and organic N. The presented results indicate that crop rotation and precipitation strongly influence NO3– concentration in tile drainwater.